The BMW model: Simple macroeconomics for closed and open economies a requiem for the IS/LM-AS/AD and the Mundell-Fleming model - Peter Bofinger; Eric Mayer; Timo Wollmershäuser (University of Würzburg, Department of Economics, 2002)
While the IS/LM-AS/AD model is still the central tool of macroeconomic teaching in most macroeconomic textbooks, it has been criticised by several economists. Colander [1995] has demonstrated that the framework is logically inconsistent, Romer [2000] has shown that it is unable to deal with a monetary policy that uses the interest rate as its operating target, Walsh [2001] has criticised that it is not well suited for an analysis of inflation targeting. In our paper we start with a short discussion of the main flaws of the IS/LM-AS/AD model. We present the BMW model as an alternative framework, which develops the Romer approach into a very simple, but comprehensive macroeconomic model. In spite of its simplicity it can deal with issues like inflation targeting, monetary policy rules, and central bank credibility. We extend the model to an open-economy version as a powerful alternative to the IS/LM-based Mundell-Fleming (MF) model. The main advantage of the open-economy BMW model is its ability to discuss the role of inflation and the determination of flexible exchange rates while the MF model is based on fixed prices and constant exchange rates. This working paper is an extended and more theoretical version of Würzburg Economic Paper No. 34. Besides describing the derivation of optimal interest rate rules and the concept of loss functions more in detail, it also discusses simple interest rate rules in an open economy as well as a strategy of managed floating within the same theoretical framework. Additionally, we explore the stabilizing properties of simple interest rate rules.
Keywords: A2; E1; E5; F41; 330; monetary policy; inflation targeting; optimal interest rate rules; simple rules; managed floating; IS/LM; Mundell-Fleming